Palliative care after the Liverpool Care Pathway: a study of staff experiences. (8th August 2019) - Collins, Heather; Raby, Peter
Abstract : The objective of this study was to explore nurses' perceptions of end-of-life care following the withdrawal of the Liverpool Care Pathway (LCP). Thirteen semi-structured interviews were conducted with nurses working in palliative care. Data were analysed using thematic analysis. Three themes emerged: perceptions of the LCP, prevailing issues, and patients' and families' experiences. This study suggested that the removal of the pathway has not remedied the issues attributed to it. Further, the way in which the LCP was removed indicates that the non-expert media can play a negative role in how palliative care is perceived, which inhibits the care process. In this respect it is important that 'insider' voices are also heard, in order to educate and also redress disinformation. Similarly, broader, persisting, contextual challenges facing staff need addressing in order to prevent a repeat of the issues leading to the removal of the LCP.